Function Classes on the Unit Disc : an Introduction. - Pavlovic, Miroslav (De Gruyter studies in mathematics., 2013)
Themonograph contains a study on various function classes, a number of new results and new or easy proofs of old result (Fefferman Stein theorem on subharmonic behavior, theorem on conjugate functions on Bergman spaces), which might be interesting for specialists, a full discussion on g-function (all p> 0), and a treatment of lacunary series with values in quasi-Banach spaces.